1975
DOI: 10.2134/agronj1975.00021962006700040002x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Nitrogen Status of Sugarbeets by Soil Analysis1

Abstract: The production of high sugar yielding crops of sugarbeets (Beta vulgaris L.) is highly dependent on available N. Excessive N fertilization is frequently cited as a cause of low sugar containing beets, which has become a problem in todays beet industry. The objective of this study was to evaluate the usefulness of N soil tests to predict N fertilizer requirements for this crop. Fertilizer trials consisting of 4 N rates (0, 70, 140, and 210 kg N/ha) were conducted on 33 farm sites in central and eastern Colorado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Close correlations between soil inorganic N and biological indices were also found by Roberts, Weaver, and Phelps (1980) and Paul and Beauchamp (1993). It seems that the inorganic N in the soil profile not only represents a quantitative value but is also a qualitative index, providing a good indication of the N-mineralization potential of a soil (Giles, Reuss, and Ludwick 1975;Roberts, Weaver, and Phelps 1980). The soil NO 3 -N in the soil profile before sowing has often been used as the basis for fertilizer N recommendations, in particular in the advisory systems of semi-arid regions (Boswell, Meisinger, and Case 1985).…”
Section: Relationship Between N-mineralization Indices and N Uptake Bmentioning
confidence: 54%
See 1 more Smart Citation
“…Close correlations between soil inorganic N and biological indices were also found by Roberts, Weaver, and Phelps (1980) and Paul and Beauchamp (1993). It seems that the inorganic N in the soil profile not only represents a quantitative value but is also a qualitative index, providing a good indication of the N-mineralization potential of a soil (Giles, Reuss, and Ludwick 1975;Roberts, Weaver, and Phelps 1980). The soil NO 3 -N in the soil profile before sowing has often been used as the basis for fertilizer N recommendations, in particular in the advisory systems of semi-arid regions (Boswell, Meisinger, and Case 1985).…”
Section: Relationship Between N-mineralization Indices and N Uptake Bmentioning
confidence: 54%
“…Soil inorganic N has frequently been found as a good indicator of the N-supply power of soils. Giles, Reuss, and Ludwick (1975) reported that the soil NO 3 -N levels measured before planting were useful in estimating the N requirements of a sugarbeet crop. Close correlations between soil inorganic N and biological indices were also found by Roberts, Weaver, and Phelps (1980) and Paul and Beauchamp (1993).…”
Section: Relationship Between N-mineralization Indices and N Uptake Bmentioning
confidence: 99%
“…, not only because of the large variability in soil N fertility (soil N supply) among fields (Goodlass et al 1996;Konno 2001;Sato et al 2008;, but also because the responses of yield and N uptake to N application rate are quite different, depending on field conditions such as soil type and organic matter application (Hasegawa and Nomura 1973;Giles et al 1975;Imura and Hayasaka 1982;Igarashi and Nakamura 1983;Nishimune 1984;Shinsenji et al 1984;Okumura et al 1989). Hence, considerable efforts have been exerted to develop an effective soil test for evaluating N fertility.…”
mentioning
confidence: 99%
“…This technique may be a precise and effective methodology for sugar beet, because sugar beet is also a deep-rooted crop as winter wheat (Suzuki and Shiga 2004). Giles et al (1975) and Bilbao et al (2004) reported that soil nitrate N test was a useful method for accessing N fertilizer rate in sugar beet production, if no organic matter was applied prior to planting sugar beet.…”
mentioning
confidence: 99%
“…A MOUNTS of residual soil NO3 reflect management, N fertilization, and irrigation practices and influence the optimal level of N fertilizer needed for sugarbeets, (Beta vulgaris L) (1,2,3,4,5). The remainder of the soil derived N is supplied through mineralization of soil organic N (1, 2, 3, 5, 11).…”
mentioning
confidence: 99%